Analysis of Production Budget Implementation As a Management Tool In Company Profit Management at PT. Sari Incofood Corporation - Budi Alamsyah Siregar; Dewi Suma (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to analyze the implementation of the production budget as a management tool in managing company profits at Pt. Sari Incofood. The research used in this research is descriptive qualitative research with secondary data. In this study, the results were obtained using the production budget at PT. Sari Incofood Corporation is still not completely perfect and has become a management tool. The Indocafe Maxtea product in 2017, 2018, and 2019 and the Indocafe Cappuccino product in 2017 can still earn a profit between the cost of production. However, the realization of production with a total of Rp. 11,660,000,000 (Favourable Variable) in the company's profit management on Indocafe Cappuccino products in 2018 and 2019 still has a detrimental difference or cannot earn a profit between the total cost of production and the realization of production with a total of Rp.785,000,000 (Unfavorable Variable).)